The legal system for threatening fines in civil lawsuits according to the Saudi system - Suliman, Randa Mustafa Hassan (Journal of Economic, Administrative and Legal Sciences, 2023)
The threatening fine is a means of financial coercion aimed at putting pressure on the obstinate debtor to force him to implement the judgment issued for real execution, which requires his intervention. It is an indirect means of compulsory real execution, and it is not a form of compensation and is not a criminal punishment, but it is a purely civil means with special features. enable it to achieve the purpose for which it was organized. A judgment of a threatening fine requires the availability of certain conditions that the execution judge competent to impose in accordance with the Saudi system verifies that they are met. The legal effects of a fine ruling are determined based on the debtor’s final position on implementation, where the fine is liquidated and its final amount is determined, which enters the state’s public treasury, without prejudice to the creditor’s right to compensation in the event that he is harmed by the debtor’s procrastination. The study aims to draw attention to the importance of the subject of the threatening fine and its impact on the implementation of judicial rulings, and to try to evaluate the Saudi system’s handling of it, and to highlight some legislative shortcomings, if any, and it also aims to contribute to enriching the Arab library with regard to the subject of the threatening fine. In order to reach conclusions and recommendations that contribute, albeit slightly, to enriching legal thought with regard to the issue of regulating a threatening fine as an indirect means of compulsory real implementation, the study relied on collecting and extracting information from its main sourcessuch as references, mothers of books, scientific papers, articles, and national legislation, and followed the descriptive analytical approach in processing and extrapolating texts from the various systems in the Kingdom of Saudi Arabia that dealt with the issue of the threatening fine in particular and judicial implementation in general. The study reached several results, including: 1- The threatening fine is not a criminal penalty and is not considered compensation for the creditor, but it is an indirect means of pressuring the obstinate debtor to implement the judgment that obliges him to implement in kind, as the amount collected from the fine is not paid to the creditor or enters the state treasury, while the creditor who is affected by the debtor’s procrastination can claim compensation. 2- The Saudi regime made the ruling of a threatening fine a permissible matter for the judge, and gave him the power to determine its amount as he deems appropriate, not exceeding the amount of ten thousand riyals per day.